Association of immune-related pneumonitis with the efficacy of PD-1/PD-L1 inhibitors in non-small cell lung cancer. (May 2020) - Cui, Pengfei; Huang, Di; Wu, Zhaozhen; Tao, Haitao; Zhang, Sujie; Ma, Junxun; Liu, Zhefeng; Wang, Jinliang; Huang, Ziwei; Chen, Shixue; Zheng, Xuan; Hu, Yi
Background: Cutaneous adverse events (AEs) have been positively associated with immune checkpoint inhibitor (ICI) efficacy in patients with melanoma, but little is known regarding the association between checkpoint inhibitor pneumonitis (CIP) and programmed cell death protein 1/programmed death ligand 1 (PD-1/PD-L1) inhibitor efficacy in non-small cell lung cancer (NSCLC). Methods: A single-institution, retrospective medical record review of patients with advanced or recurrent NSCLC who were treated with PD-1/PD-L1 inhibitors between 1 September 2015 and 1 June 2019 was conducted. A total of 276 NSCLC patients with or without immune-related pneumonitis who received at least one dose of ICIs and had at least one follow-up visit were identified. Kaplan–Meier curves of the progression-free survival (PFS) of patients stratified according to immune-related pneumonitis development were evaluated with the log-rank test as a preplanned primary objective. Multivariate analysis of PFS was performed with Cox proportional hazard regression models. Results: In the cohort of 276 patients, 42 patients developed CIP attributed to PD-1/PD-L1 inhibitors. Survival analysis showed that the overall response rate was significantly higher in patients with CIP than in those without CIP (61.90% versus 29.91%, respectively, p < 0.01), and that CIP development was significantly associated with increased PFS (45.80 weeks versus 21.15 weeks, respectively, p < 0.01). Additionally, 16-week landmark analysis produced the same results. Similarly, subgroup analysis of PD-1 inhibitor-treated, nivolumab-treated, and pembrolizumab-treated groups also revealed that CIP increased survival in NSCLC patients. Additionally, grade 1–2 pneumonitis showed an association with increased ICI efficacy in NSCLC; however, grade 3–4 pneumonitis did not. In addition, only two of the four pneumonitis radiological subtypes showed associations with increased ICI efficacy in NSCLC. Conclusion: CIP is associated with enhanced PD-1/PD-L1 inhibitor efficacy in NSCLC patients. Grade 1–2 pneumonitis and the radiological features of hypersensitivity and cryptogenic organizing pneumonia (COP) may be signs of enhanced ICI efficacy. However, further studies with larger numbers of patients and longer follow-up times are needed to validate our findings.